Helping the Web help the disabled. - Lazzaro, J.J (IEEE spectrum)
The World Wide Web's two chief problems for the disabled are poor page design and browsers that do not work well with adaptive equipment. Consequently, lists of do's and don'ts have been compiled to steer the page designer in applying adaptive technology. A selection of such guidelines is given. For most people today, getting to the Web means using some kind of computer. While a system that is useful to the disabled only when they are on the Web can certainly be set up, a more practical approach is to have a computer that is ?disabled-friendly? both on and off the Internet. Such a computer can then be used not only for Web surfing, but also for e-mail, word processing, database management, spreadsheets, and all the other sorts of tasks for which the nondisabled use computers. Thus the first thing to examine is how the computer industry is serving the needs of the disability community. Some of the adaptive technology available for disabled people are discussed including improved computer displays, screen readers, Braille displays, voice input systems and browser developments